2011
DOI: 10.1130/g32596.1
|View full text |Cite
|
Sign up to set email alerts
|

Latest Permian mercury anomalies

Abstract: A sedimentary record from the Buchanan Lake section, Canadian High Arctic, shows anomalous high levels of mercury (Hg) during the latest Permian extinction (LPE) on northwest Pangea. Signifi cant infl ux of Hg progressively overwhelmed the marine system. Major disruption of the organic matter-mediated Hg drawdown process resulted in accumula-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
287
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(298 citation statements)
references
References 31 publications
10
287
1
Order By: Relevance
“…However, one of the challenges that remains is to fi nd a primary marker for the volcanism within these same archives, allowing a clear causal relationship to the environmental perturbation to be developed, rather than purely markers indicating environmental change. Recent efforts in this area have included the use of osmium isotopes (Ravizza and Peucker-Ehrenbrink, 2003;Robinson et al, 2009) and mercury (Sanei et al, 2012;Silva et al, 2014).…”
mentioning
confidence: 99%
“…However, one of the challenges that remains is to fi nd a primary marker for the volcanism within these same archives, allowing a clear causal relationship to the environmental perturbation to be developed, rather than purely markers indicating environmental change. Recent efforts in this area have included the use of osmium isotopes (Ravizza and Peucker-Ehrenbrink, 2003;Robinson et al, 2009) and mercury (Sanei et al, 2012;Silva et al, 2014).…”
mentioning
confidence: 99%
“…The largest volcanic eruption in Earth history, the Siberian Traps, combined with 517 combustion of organics in the Tunguska Basin, would have had an extremely high metal loading 518 rate that far exceeds normal background. As an example (Sanei et al, 2012) calculated a Hg 519 loading rates from the Siberian Traps that would be 4x above modern anthropogenic emissions, 520 assuming a 500 ky eruption period. Similar estimates for other metal fluxes can be made based 521 on the metal/S ratio for modern volcanic emissions (Nriagu, 1989), and estimates of total SO 2 522 release of 3.8 × 10…”
mentioning
confidence: 99%
“…Sanei et al 17 demonstrated that the Siberian Trap eruption, the largest LIP in the geologic record and also associated with the largest Phanerozoic extinction event, left a characteristic mercury spike as a fingerprint in the rock record. Subsequent work has confirmed Hg spikes associated with other LIP events associated with mass extinction intervals [18][19][20][21][22][23] .…”
Section: Mercury As a Proxy For Lip Eventsmentioning
confidence: 99%
“…Organic matter (OM) has a strong capacity for 1 absorbing dissolved Hg in marine conditions 21 , whereby Hg deposited in the ocean through wet and dry fall is mainly captured by OM and sequestered into sediments through geologic time. Excess mercury flux to the environment during periods of major volcanic eruption can overwhelm this natural system, creating a mercury spike relative to total organic carbon (TOC) in the rock record 17 , as a key indicator of massive volcanism. Hg stable isotope data can further verify a volcanic source of Hg spikes 20,24 .…”
Section: Mercury As a Proxy For Lip Eventsmentioning
confidence: 99%
See 1 more Smart Citation